ANALISIS TENTANG GHARAR DALAM PENGGUNAAN METODE PENCATATAN AKRUAL AKUNTANSI BANK MUAMALAT CABANG SURABAYA - YULFIA, ANA (Jurnal Akuntansi AKUNESA, 2013)
Islamic banks using the accrual method of record-keeping that much debated asit contains elements of gharar (obscurity), where transactions in keterjadian atthe time, admit that many people assume that banks do window dressing. Thisresearch using the method deskriptip. Accrual accounting does not containelements of gharar because if the cost burden is to earn an income or financialyear period reported, eraric unpaid to be reckoned with because it is already arights or obligations that entities for recognition of income for Bank Muamalatadheres to the principle of time value of money.Key words: Gharar, the methodof recordingthe accrualbasisof Islamic banks